Mechanistic studies of tumor-associated macrophage immunotherapy - Cao, Jiandong; Liu, Chengsen (Frontiers in Immunology, 2024)
Tumor-associated macrophages (TAMs) are present in the tumor microenvironment and can polarize into subtypes with different functions and characteristics in response to different stimuli, classifying them into anti-tumorigenic M1-type and pro-tumorigenic M2-type. The M1-type macrophages inhibit tumor growth through the release of pro-inflammatory cytokines, whereas the M2-type macrophages contribute to tumor progression through the promotion of tumor proliferation, angiogenesis and metastasis. Due to the duality of macrophage effects on tumors, TAMs have been a hot topic in tumor research. In this paper, the heterogeneity and plasticity of TAMs, the interactions between TAMs and other immune cells, and the effects of TAMs on tumors are reviewed, and the therapeutic strategies for TAMs are summarized and discussed. These therapeutic strategies encompass methods and approaches to inhibit the recruitment of TAMs, deplete TAMs, and modulate the polarization of TAMs. These studies help to deeply understand the mechanism of TAMs-tumor interaction and provide reference for combination therapy of tumors.